Prosthetic Rehabilitation of the Partially Edentulous Atrophic Posterior Mandible with Short Implants (≤ 8 mm) Compared with the Sandwich Osteotomy and Delayed Placement of Standard Length Implants (> 8 mm): a Systematic Review - Thomas Starch-Jensen; Helle Baungaard Nielsen (Stilus Optimus, 2018)
Objectives: Test the hypothesis of no difference in prosthetic rehabilitation of the partially edentulous atrophic posterior mandible with short implants (≤ 8 mm) compared with the sandwich osteotomy and delayed placement of standard lengths implants (> 8 mm). Material and Methods: A MEDLINE (PubMed), Embase and Cochrane library search in combination with a hand-search was conducted by including studies published in English. No year of publication restriction was applied. Results: Six randomized controlled trials characterized by low or moderate risk of bias fulfilled the inclusion criteria. There were no statistically significant differences (P > 0.05) in the survival rate of suprastructures and implants between the two treatment modalities after one year. Sandwich osteotomy and delayed implant placement demonstrated statistically significant higher long-term peri-implant marginal bone loss as well as biological and technical complications compared with short implants (P < 0.0001). Moreover, patients significantly favoured prosthetic rehabilitation with short implants (P < 0.0001). Conclusions: Short implants and the sandwich osteotomy with delayed placement of standard length implants appear to result in predictable outcomes in terms of high survival rate of suprastructures and implants after prosthetic rehabilitation of the partially edentulous atrophic posterior mandible. However, further long-term randomized controlled trials assessing donor site morbidity, an economic perspective, professional and patient-related outcome measures with the two treatment modalities are needed before definite conclusions can be provided about the beneficial use of short implants for prosthetic rehabilitation of the partially edentulous atrophic posterior mandible compared with the sandwich osteotomy and delayed placement of standard length implants.